Perempuan dalam Prostitusi: Konstruksi Pelindungan Hukum Terhadap Perempuan Indonesia dari Perspektif Yuridis dan Viktimologi (Women in prostitution: Construction of Legal Protection Towards Indonesian Women from a Juridical and Victimitarian Perspective) - Yaris Adhial Fajrin; ach faisol triwijaya (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2019)
The practice of prostitution involving women as the main perpetrator creates a negative stigma that sees women as guilty persons. Even though there are also women who are involved in the practice of prostitution due tocoercion. This condition creates a bias towards the position of the victim in the practice of prostitution. This paper is to examine the involvement of women in the practice of prostitution while also recognizing the position of women that are involved in the practice of prostitution. This research uses the normative juridical research method. Women in the prostitution network can be identified as victims due to both internal and external pressure.Women are perpetrators if involved without any pressure from other parties. Women are victims if they act as service providers, suffered, because of force by power from others, besides the relative requirements of women as victims of prostitution when involved in the practice of prostitution because they have been victims of sexual violence and make prostitution as livelihoods. Thus, it is hoped that legislators will soon be able to formulate limits on victims in the context of legal reform and just law enforcement. AbstrakPraktik prostitusi yang melibatkan perempuan sebagai aktor utama menimbulkan stigma negatif yang memandang perempuan sebagai insan yang bersalah. Padahal adapula perempuan yang terlibat dalam praktik prostitusi diakibatkan keterpaksaaan. Kondisi ini menimbulkan bias terhadap kedudukan korban dalam praktik prostitusi. Tulisan ini untuk mengkaji keterlibatan perempuan dalam praktik prostitusi sekaligus mengetahui kedudukan perempuan yang terlibat dalam praktik prostitusi. Penelitian ini menggunakan metode penelitian yuridis normatif. Perempuan dalam jaringan prostitusi dapat teridentifikasi sebagai korban akibat tekanan internal maupun eksternalnya. Perempuan sebagai pelaku apabila terlibat tanpa tekanan dari pihak di luar dirinya. Perempuan sebagai korban apabila bertindak sebagai pemberi jasa, menderita, karena dan daya paksa dari orang lain, selain itu syarat relatif perempuan sebagai korban dalam prostitusi manakala terlibat dalam praktik prostitusi karena pernah menjadi korban kekerasan seksual dan prostitusi sebagai mata pencaharian. Diharapkan pembentuk undang-undang segera mungkin untuk merumuskan mengenai batasan korban dalam rangka pembaharuan hukum dan penegakan hukum yang berkeadilan.